Implementation of Green IT-Based Cloud Computing for Energy Efficiency in Technology Companies - Judijanto, Loso; Wijaya, Hamid; Ismail, Rima Ruktiari; Vandika, Arnes Yuli (West Science Information System and Technology, 2025)
The growing demand for energy-efficient and sustainable solutions has positioned Green IT-based cloud computing as a pivotal strategy for technology companies aiming to balance operational efficiency with environmental stewardship. This study conducts a systematic literature review of 15 Scopus-indexed documents to explore the benefits, challenges, and strategies associated with the adoption of Green IT-based cloud computing. The findings reveal that these practices significantly enhance energy efficiency, reduce operational costs, and minimize carbon footprints. However, challenges such as high implementation costs, technological complexity, and intermittent renewable energy sources impede widespread adoption. Strategies including the use of AI and machine learning, collaborations with renewable energy providers, and the establishment of standardized policies are identified as effective solutions. This study contributes to the growing discourse on sustainable IT practices and provides a roadmap for technology companies aiming to integrate Green IT principles into their cloud computing operations.